Gene Expression Profile Analyses of the Skin Response of Balb/c-Nu Mice Model Injected by Staphylococcus aureus - Zhang J; Wang C; An Q; Quan Q; Li M; Zhao D (Dove Medical Press, 2022)
Jiachan Zhang,1 Changtao Wang,1 Quan An,2 Qianghua Quan,2 Meng Li,2 Dan Zhao1 1Beijing Key Lab of Plant Resource Research and Development, College of chemistry and materials engineering, Beijing Technology and Business University, Beijing, 100048, People's Republic of China; 2Yunnan Baiyao Group Co., Ltd., Kunming, 650000, People's Republic of ChinaCorrespondence: Changtao Wang, Beijing Key Lab of Plant Resource Research and Development, College of chemistry and materials engineering, Beijing Technology and Business University, Fucheng Road, Beijing, 100048, People's Republic of China, Tel +8610-68984917, Email wangct@th.btbu.edu.cn Quan An, Yunnan Baiyao Group Co., Ltd., Kunming, 650000, People's Republic of China, Email 59304376@qq.comBackground: Pathogenesis and persistence of many skin diseases are related to Staphylococcus aureus (S. aureus) colonization. S. aureus infection can cause varying degrees of changes in cell gene expression, resulting in complex changes in cell phenotype and finally changes in cell life activities.Materials and Methods: The transcriptomes of healthy and Staphylococcus aureus (S. aureus)-infected murine skin tissues were analyzed. We identified 638 differentially expressed genes (DEGs) in the infected tissues compared to the control samples, of which 324 were upregulated and 314 were downregulated, following the criteria of P < 0.01 and |log2FC| > 3. The DEGs were functionally annotated by Gene Ontology (GO), KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway and the protein-protein interaction (PPI) network analyses.Results: The upregulated DEGs were mainly enriched in GO terms, such as response to stimulus, immune system process and signal transduction, as well as in the complement and coagulation cascade pathway. Thus, S. aureus infection likely activates these pathways to limit the influx of neutrophils and prevent skin damage. Four clusters were identified in the PPI network, and the major hubs were mainly related to cell cycle and proliferation, and mostly downregulated. The expression levels of Nox4, Mmrn1, Mcm5, Msx1 and Fgf5 mRNAs were validated by qRT-PCR and found to be consistent with the RNA-Seq data, confirming a strong correlation between the two approaches.Conclusion: The identified genes and pathways are potential drug targets for treating skin inflammation caused by S. aureus and should be investigated further.Keywords: Staphylococcus aureus, inflammation, gene expression profile, transcriptome